URUN DAYA MASYARAKAT DALAM REAKTUALISASI KIPO SEBAGAI JAJANAN KHAS KOTAGEDE YOGYAKARTA - Imam Basthomi; Siti Nur Laili Rahmawati (UIN Sunan Kalijaga, 2022)
One of the richness of Indonesian culture is reflected in the diversity of traditional local foods that are consumed by the community. Along with the times, the existence of most local food is increasingly threatened. One of them is Kipo, a traditional snack from Yogyakarta. As the first step to preserve it, this article explores in-depth to get to know Kipo and find out the opportunities and challenges faced to survive as one of the typical snacks from Yogyakarta. Based on empirical research (Field Research) with data collection through interviews, observations, and literature studies, it was found that Kipo is one of the traditional snacks of Kotagede which has historical and cultural values. Its existence has the potential to be developed into an attraction for culinary tourism activities. To make this happen, it takes the cooperation of the government and local residents to rebrand the Kipo. And what should not be left behind is utilizing mass media and the internet to support the process of information dissemination and promotion